2019
DOI: 10.1111/apa.14754
|View full text |Cite
|
Sign up to set email alerts
|

Skin‐to‐skin contact the first hour after birth, underlying implications and clinical practice

Abstract: Aim This paper integrates clinical expertise to earlier research about the behaviours of the healthy, alert, full‐term infant placed skin‐to‐skin with the mother during the first hour after birth following a noninstrumental vaginal birth. Method This state‐of‐the‐art article forms a link within the knowledge‐to‐action cycle, integrating clinical observations and practice with evidence‐based findings to guide clinicians in their work to implement safe uninterrupted skin‐to‐skin contact the first hours after bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
156
1
19

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(211 citation statements)
references
References 102 publications
2
156
1
19
Order By: Relevance
“…Evidence supporting the practice of post-birth skin-to-skin contact (SSC) is strong, suggesting multiple benefits for both mother and child. Advantages for the mother include early elimination of the placenta, reduced bleeding, improved self-efficacy of breastfeeding, and decreased maternal stress [9]. Advantages for the infant include a reduction in the negative consequences of "stress of birth", more appropriate thermoregulation, persisted even in the first days and less crying [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence supporting the practice of post-birth skin-to-skin contact (SSC) is strong, suggesting multiple benefits for both mother and child. Advantages for the mother include early elimination of the placenta, reduced bleeding, improved self-efficacy of breastfeeding, and decreased maternal stress [9]. Advantages for the infant include a reduction in the negative consequences of "stress of birth", more appropriate thermoregulation, persisted even in the first days and less crying [9].…”
Section: Introductionmentioning
confidence: 99%
“…Advantages for the mother include early elimination of the placenta, reduced bleeding, improved self-efficacy of breastfeeding, and decreased maternal stress [9]. Advantages for the infant include a reduction in the negative consequences of "stress of birth", more appropriate thermoregulation, persisted even in the first days and less crying [9]. Another factor is incubator time defined as the amount of time in the incubator needed to achieve thermal stability [10].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported in other studies that it takes at least 1 hour for newborn infants in skin-to-skin contact to locate the nipple and start suckling (Widström et al, 1987;. During this hour, the infant gets acquainted with the mother (Widström et al, 2019) and prepares the mother to produce milk (Matthiesen et al, 2001). In another study by the same group, it was found that ReseaRch © 2020 MA Healthcare Ltd breastfeeding occurred around 70 minutes after birth in an unmedicated group of infants (Nissen et al, 1995), suggesting that infant-directed initiation of breastfeeding may take longer than 1 hour.…”
Section: Discussionmentioning
confidence: 98%
“…Widström et al. bridge the gap between research knowledge and clinical practice about skin‐to‐skin contact between mothers and infants during the first hour after birth. They report that this elicits the infant's internal process as they go through nine instinctive states and contributes to early coordination of the infant's five senses and movement.…”
Section: Skin‐to‐skin Contact In the First Hour After Birth Has A Posmentioning
confidence: 99%